Effects of non-wetting fraction and pitch distance in flow boiling heat transfer in a wettability-patterned microchannel. (July 2022) - Wang, Hongzhao; Yang, Yinchuang; Wang, Ying; Chao, Christopher Y.H.; Qiu, Huihe
Highlights: The effects of non-wetting fraction and pitch distance of adjacent dots on flow boiling heat transfer and pressure drop are characterized. Bubbles coalesced more easily, and flow patterns transited faster in the microchannel with smaller pitch distance. HTC, CHF and pressure drop are found to significantly rely on the pitch distance of dots and the mass flux. Bubble detachment diameters are predicted in hydrophilic, hydrophobic, and wettability-patterned microchannels, respectively. Abstract: Flow boiling in microchannels offers a promising and attractive solution for thermal management of electronic devices and power systems. In this paper, microchannels composed of a hydrophilic surface with hydrophobic dots were studied to characterize the effects of non-wetting fraction and pitch distance of adjacent dots on flow boiling heat transfer and pressure drop. The pitch distances ranging from 122 µm to 172 µm were studied. Using deionized water as the working fluid, highly subcooled flow boiling experiments were conducted at different mass fluxes ranging from 41.1 to 246.6 kg/m 2 s over a heat flux up to 146.2 W/cm 2 . Bubble dynamics and flow patterns were visualized using a high-speed camera. It was found that bubbles coalesced more easily, and flow patterns transited faster in the microchannel with smaller pitch distance. Heat transfer coefficient (HTC), critical heat flux (CHF) and pressure drop were found to significantly rely on the pitch distance of dots and the mass flux. Furthermore, based on a force-balance model, bubble detached diameters were predicted in hydrophilic, hydrophobic and wettability-patterned microchannels, respectively. This provides a useful insight to optimize the wettability pattern design and then improve flow boiling heat transfer in a microchannel.